Evaluating fugacity models for trace components in landfill gas. - Shafi, Sophie; Sweetman, Andrew; Hough, Rupert L.; Smith, Richard; Rosevear, Alan; Pollard, Simon J. T. (Elsevier Science B.V., Amsterdam., 2006)
A fugacity approach was evaluated to reconcile loadings of vinyl chloride (chloroethene), benzene, 1,3-butadiene and trichloroethylene in waste with concentrations observed in landfill gas monitoring studies. An evaluative environment derived from fictitious but realistic properties such as volume, composition, and temperature, constructed with data from the Brogborough landfill (UK) test cells was used to test a fugacity approach to generating the source term for use in landfill gas risk assessment models (e.g. GasSim). SOILVE, a dynamic Level II model adapted here for landfills, showed greatest utility for benzene and 1,3-butadiene, modelled under anaerobic conditions over a 10 year simulation. Modelled concentrations of these components (95 300 μg m−3; 43 μg m−3) fell within measured ranges observed in gas from landfills (24 300–180 000 μg m−3; 20–70 μg m−3). This study highlights the need (i) for representative and time-referenced biotransformation data; (ii) to evaluate the partitioning characteristics of organic matter within waste systems and (iii) for a better understanding of the role that gas extraction rate (flux) plays in producing trace component concentrations
Keywords: Landfill gas; Risk assessment; Fugacity; Emissions modelling; Landfill gases